2019
DOI: 10.1002/adts.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Open Systems: Construction of a Mean‐Field Particle Reservoir

Abstract: The simulation of open molecular systems requires explicit or implicit reservoirs of energy and particles. Whereas full atomistic resolution is desired in the region of interest, there is some freedom in the implementation of the reservoirs. Here, a combined, explicit reservoir is constructed by interfacing the atomistic region with regions of point-like, non-interacting particles (tracers) embedded in a thermodynamic mean field. The tracer molecules acquire atomistic resolution upon entering the atomistic reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 56 publications
1
67
0
Order By: Relevance
“…The minimal size of the atomistic region in AdResS which delivers structural properties faithfully reproducing those calculated in a full atomistic simulation of reference defines the region where the atomistic or chemical degrees of freedom are strictly required for the properties analyzed. The technical innovation of this work is the use of the most recent version of AdResS where the majority of the system's reservoir, TR, is represented by noninteracting, pointlike tracer particles with a direct coupling to the transition region [7]. Given the molecular complexity of the system considered in this .…”
Section: B Definition Of the Relevant Atomistic Degrees Of Freedom Vmentioning
confidence: 99%
See 3 more Smart Citations
“…The minimal size of the atomistic region in AdResS which delivers structural properties faithfully reproducing those calculated in a full atomistic simulation of reference defines the region where the atomistic or chemical degrees of freedom are strictly required for the properties analyzed. The technical innovation of this work is the use of the most recent version of AdResS where the majority of the system's reservoir, TR, is represented by noninteracting, pointlike tracer particles with a direct coupling to the transition region [7]. Given the molecular complexity of the system considered in this .…”
Section: B Definition Of the Relevant Atomistic Degrees Of Freedom Vmentioning
confidence: 99%
“…A water molecule leaving the region and entering the TR region is mapped onto a virtual site whose trajectory corresponds to the dynamics of the tracer while the atoms of the water molecule are rigidly bound to the site and their equations of motion are no longer considered. In our previous work [7] we have shown that for a liquid of pure water at room conditions, the cooperative action of the thermodynamic force and of the thermostat assures proper equilibrium throughout the system and allows for accurate structural and dynamical properties to be calculated in the AT region. The extreme simplification of the computational setup became possible through the mapping of the algorithm onto a theoretical model of open system.…”
Section: Basic Principles Of Adress and The Criteria For An Openmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas molecules are added to and removed from the reservoir in events that resemble GCMC insertion and deletion moves, which fixes the chemical potential (and, hence, the pressure) of the remainder of the simulation cell once the system has adequately equilibrated. Readers can consult work by the group of Parrinello [7577] for details of the general approach or others [7880] for specific applications to adsorption of gases in porous materials.…”
Section: Molecular Models and Methodsmentioning
confidence: 99%